Development and evaluation of a voluntary education module on medicine safety for basic science medical students in Nepal - Palaian, Subish; Shankar, Pathiyil Ravi; Chhetri, Sanjaya Khatri (Journal of Pharmacy Practice and Community Medicine)
Dear Editor, Although medicines are beneficial, sometimes they can be harmful and can lead to potentially life threatening conditions and even lead to death. Medicines can cause Adverse Drug Reactions (ADRs), which has been defined by the World Health Organization (WHO) as ‘a response to a drug which is noxious and unintended, and which occurs at doses normally used in man for the prophylaxis, diagnosis, or therapy of disease or for the modification of physiological function’. Data suggests ADRs to be a major cause of morbidity and mortality worldwide. Evidence suggests knowledge, attitude and practice towards ADR reporting and prevention among health professionals including medical doctors are poor.